Minor Procedure, Measurable Impact: Symptom Improvement after Urethral Meatotomy in Peshawar, Pakistan - Amir Taimur Khan, Hazratullah, Hamza Khan Shahbazi, Syed Muhammad Haider, Moath Ahmad Abdullah Almuradi, Muhammad Aness Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Urethral meatotomy is a frequently used surgical treatment for meatal stenosis but remains poorly studied in regard to patient-reported outcomes (PROs), especially in South Asian populations. The purpose of this study is to determine the degree of symptom improvement and the reasons for different outcomes after urethral meatotomy at Khyber Teaching Hospital in Peshawar, Pakistan. Methods: A prospective survey was sent out to families of boys who had undergone urethral meatotomy between August 2022 and September 2023. Symptom change was measured using a 5-point Likert scale where 5 indicated “much improved” and 1 meant “much worse.” Chart reviews gave clinical detail surrounding the surgery such as indication for surgery (e.g., abnormal stream, dysuria, storage symptoms), suture use, complications, and reoperations. Generalized estimating equations examined the relationships between variables and the improvement in symptoms. Results: Out of 629 surveys, 194 were returned (30.8%) with 182 having analyzable data. The majority of patients were under age 12 (87%) and had private insurance (74%). The most common indication for surgery was abnormal stream (72%). Eighty-six percent of the patients “much improved” while 16% “somewhat improved” and 4% had no improvement or worsening. Some of the complications (4.9%) were granulomas and infections while the reoperation rate for restenosis was 2.2%. Patients having preoperative abnormal streams had greater chances of improvement (OR 1.83, p =0.014). There was no difference in outcomes with or without suture (p >0.05). Conclusion: There is improvement in the outcomes following Urethral meatotomy in this Pakistani cohort with Meatal stenosis and is required with stream abnormalities. Its ease of use and minimal complication percentage (4.9%) highlight how it can be useful where resources are limited. Techniques which do not require sutures provide the same results, supporting their use in reducing the required Keywords: Meatotomy, reported outcomes, Khyber Teaching Hospital, Peshawar, Pakistan.